Experimental investigations on laser cladding of NiCrBSi + WC coating on SS410. (2020) - Gowtham, A.; Chaitanya, G.; Katiyar, Jitendra Kumar; Chandak, Aayush; Gupta, T.V.K.
Abstract: Laser cladding is an emerging technology for depositing coating material over the substrate with less dilution (<5%) and good metallurgical bonding with low heat affected zone. The Ni-based alloys are very popular for high-temperature wear applications and with addition of tungsten carbides increase the hardness. This also has high melting point with low coefficient of thermal expansion and high wettability with the metal matrix. The powder used for cladding is fused tungsten carbide (WC) (60% wt) mixed with Ni-alloy (40% wt). Metal matrix composite (MMC) coating is made on Stainless Steel (SS410) substrate using a co-axial fiber laser for varying process parameters. The process parameters are optimized and found that, at 3.6 kW power and 65 g/min powder feed rate, a good quality clad is obtained. The microstructure characterization of the cladded samples is carried with a scanning electron microscope (SEM). The results show that laser cladding has a good metallurgical bonding with the substrate and the SEM images reveal the presence of γ-Ni dendrite structure and particles of WC in Ni matrix. The WC particles in the Ni-matrix are considerably improving the hardness of the composite. The average micro-hardness obtained in the present work is of 390 HV and 1900 HV for the Ni-matrix and WC respectively.